7 - Les politiques de développement élaborées par la Banque mondiale à l’intention des pays de l’hémisphère sud de 1980 à nos jours : origines, variantes et implications - Diop, Aladji Madior (Africa Development, 2021)
In the 1980s, 1990s and 2000s, the World Bank gradually drew up what its “experts” considered as a new development paradigm for countries of the Southern hemisphere. This new paradigm included two generations of reforms. Based on the World Development Reports over the three decades and writings of eminent thinkers such as Jean Ziegler, Samir Amin, etc., this article intends to further examine the main criticisms made by the World Bank experts over the development policies prevailing in the 1970s. It thus lays out both ends of the first generation of reforms proposed to southern countries in terms of comprehensive development model and proposals for sectoral reforms. Finally, it analyses the second generation of reforms drawn up by the World Bank and the sectoral policies (the “what” and the “how”) recommended for countries of the Southern hemisphere. Hence, the link is established between these two generations of reforms and their relevance analyzed.